1989
DOI: 10.1002/1097-4679(198901)45:1<114::aid-jclp2270450117>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Turkish and Anglo-American normative data on the Wechsler memory scale

Abstract: This study compared the performance of 200 Turkish adults, divided by educational status and age (20‐39; 40‐59), with published data based upon similar‐aged American and British normative samples. Results highlighted the major influence of educational background in determining performance on the WMS and the implications of this effect in interpreting normative performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…In terms of educational effects, while it is known that level of education tends to impact to a greater degree on language than on visuographic tests, it is yet influential on both of these functional modalities as has been demonstrated on cognitive tests generally (Lezak et al, 2004;Mitrushina et al, 2005), as well as specifically in respect of the targeted Associate Learning and Visual Reproduction subtests on the Wechsler Memory Scale (Gilleard & Gilleard, 1989;Lezak, 1983). In particular, for both the Associate Learning 'easy' and 'hard' pairs, it has been shown that participants with a higher level of education outperform those with lower levels of education (Ivnik et al, 1992).…”
Section: Age Sex and Education Effectscontrasting
confidence: 58%
See 4 more Smart Citations
“…In terms of educational effects, while it is known that level of education tends to impact to a greater degree on language than on visuographic tests, it is yet influential on both of these functional modalities as has been demonstrated on cognitive tests generally (Lezak et al, 2004;Mitrushina et al, 2005), as well as specifically in respect of the targeted Associate Learning and Visual Reproduction subtests on the Wechsler Memory Scale (Gilleard & Gilleard, 1989;Lezak, 1983). In particular, for both the Associate Learning 'easy' and 'hard' pairs, it has been shown that participants with a higher level of education outperform those with lower levels of education (Ivnik et al, 1992).…”
Section: Age Sex and Education Effectscontrasting
confidence: 58%
“…Further, it is noteworthy that the score of 12.63 for the present study is lower than the obtained scores of around 15 to 16 for the Kear-Colwell and Heller study for their 35 to 64 year old group, and the Bigler et al data for their 36 to 50 year old group, despite the age disadvantage of these groups that include much older adults than the present study into the 50s and 60s (both cited in Mitrushina et al, 2005). Again the norms for the present study were somewhat higher than those for the Gilleard and Gilleard (1989) study on a Turkish group with nil to elementary level that spans the 20 to 39 age group (present study Mean = 12.63 versus the comparative study mean of 11.22).…”
Section: Between-studies Normative Comparisonsmentioning
confidence: 61%
See 3 more Smart Citations